Material properties of partially pregelatinized cassava starch prepared by mechanical activation - Zhang, Yanjuan; Huang, Zuqiang; Yang, Cong; Huang, Aimin; Hu, Huayu; Gong, Zhanqiang; Sun, Guosong; Huang, Kelin (Die Stärke, 2013)
This study has focused on the preparation of partially pregelatinized cassava starch (PPCS) by mechanical activation (MA) using a customized stirring ball mill. The changes in degree of gelatinization, crystal structure, particle size, surface morphology, powder characteristics, and pasting properties of cassava starch mechanically activated for different time were investigated by various characterizations. The results showed that MA could significantly destroy the crystal structure of starch granules, contributing to the increase of cold‐water solubility, flowability, and floodability, the variations of particle size and surface morphology, and the decrease in pasting temperature, viscosity of cooked PPCS paste, breakdown, and setback. It was also found that the PPCS with different degree of gelatinization could be prepared by controlling the milling time. With the unique properties induced by MA, the potential use of PPCS as excipient in pharmaceutical formulations is discussed.